Third Article Theology : A Pneumatological Dogmatics - Habets, Myk (Book collections on Project MUSE., 2016)
Third Article Theology (TAT) is the name given to a new movement in constructive theology utilizing a distinctly pneumatological approach to dogmatics. Trinitarian in its foundation, pneumatological in its impetus, and comprehensive in its scope, TAT specifies both a method and a theology. Thinking through the theological loci of the tradition in relation to the Holy Spirit opens up new vistas and a deeper vision of the task of theology, revealing ways of thinking hitherto eclipsed by the tradition. Drawing upon the trinitarianism of the Great Tradition, theologians from across the theological spectrumbring their voices to bear upon central and defining theological issues of today in order to present a new form of systematic theology--a pneumatological dogmatics--capable of representing the faith in a contemporary mode. For students, scholars, and clergy, the volume unfolds the classic articles of systematic theology in this new register. Each doctrinal article is written by a leading theologian in the field, with essays from Amos Yong, Eugene Rogers, Veli-Matti Karkkainen, Joel Green, Marc Cortez, Frank Macchia, Myk Habets, and others.